Protagonist and deuteragonist-based video indexing and retrieval system for movie and video song sequences. (4th November 2019) - Ratanpara, Tushar; Patel, Narendra M.
Protagonist and deuteragonist are two main characters that plays leading role in Indian Hindi movie (IHM). Currently such information is attached using textual caption which is highly unreliable. The research presented in this paper is to automatically index and retrieve the content based on protagonist and deuteragonist from the large IHM and video song sequences (VSS). Video song sequence indexes are extracted using audio-based approach from IHM in module 1. These indexes are used as an input in module 2. Faces are identified from every VSS. Colour histogram and spatiogram descriptor are extracted from faces. Similarity between two faces is computed using Bhattacharyya coefficient. Similarity-based clustering technique is performed to obtain clusters of faces. Recognition of protagonist and deuteragonist is done using surf feature points. The experimental results are carried out using Indian Hindi movies of different genres.